อันตรกิริยาของพืชสมุนไพรที่มีฤทธิ์ต้านเบาหวานในพื้นที่ของโครงการอนุรักษ์พันธุกรรมพืช อันเนื่องจากพระราชดำริฯ กับหน้าที่การทำงานของพี-ไกลโคโปรตีน - สุรีย์ เจียรณ์มงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this study was to investigate and compare the effect of 4 herbal plants in the Plant Genetic Conservation Project area under The Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn on the function of P-glycoprotein, using the in vitro model of the Caco-2 cells. The plants were selected into this study by its ability to inhibit α-glucosidase, which is a drug target for diabetic control. These plants included Pterospermum littorale Craib (Family Sterculiaceae); Dialium cochinchinense Pierre (Family Fabaceae); Mamecylon plebejum Kurz. Var ellipsoideum Craib. (Family Melastomataceae) and Thespesia populnea (L.) Soland. Ex Corr. (Family Malvaceae). The function of P-glycoprotein was assessed by measuring the intracellular calcein accumulation in the Caco-2 cells dultured for 21 days. The results demonstrated that extracts of Mamecylon plebejum and Pterospermum littorale at the highest concentration in this study were unable to affect the activity of P-glycoprotein. On the other hand, extracts of Dialium cochinchinense and Thespesia populnea inhibited the P-glycoprotein function in comparable potency by 2-3 folds. The inhibitory actions of the two extracts were concentration dependent. Hence, it was possible that Dialium cochinchinense and Thespesia populnea might be able to cause problems regarding P-glycoprotein-mediated drug interactions through the direct inhibition of this efflux pump. Further studies in this regard are needed.